Biosynthesis and Regulation of Grisemycin, a New Member of the Linaridin Family of Ribosomally Synthesized Peptides Produced by Streptomyces griseus IFO 13350 - Claesen, Jan (American Society for Microbiology, 2011)

(untitled)
Our recent identification and genetic analysis of the biosynthetic gene cluster for production of the ribosomally synthesized and posttranslationally modified peptide cypemycin revealed a new class of peptide natural products, the linaridins. Here we describe the identification and characterization of grisemycin, a linaridin produced by a previously unidentified gene cluster in Streptomyces griseus IFO 13350. Mass spectrometric analysis revealed that grisemycin possesses at least three of the modifications found in cypemycin, as well as an analogous leader peptidase cleavage site. Expression of putative grisemycin biosynthetic genes in a Streptomyces coelicolor A3(2) derivative, combined with deletion of the gene encoding the grisemycin precursor peptide, confirmed the identity of the grisemycin gene cluster. Both grisemycin and cypemycin depend on the transcriptional activator AdpA for wild-type levels of production.